E-Commerce in a Public Policy Perspective - Kusuma, Aji Ratna; Prihatiningsih, Endang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Sharing economy activity in the modern technology is now applied in the form of e-commerce or online business which then becomes a new trading phenomenon that is growing rapidly in various fields according to the demands of society. In Indonesia itself, e-commerce is growing rapidly along with the use of android /iOS-based telecommunications media and increasingly affordable internet access costs. Like conventional types of commerce, e-commerce has the accompanying positive and negative impacts, especially about investment issues, labor and their effects on conventional businesspeople. This is where the government's role as a regulator in this case is needed. However, policies issued by the Government are often unresponsive and seem slow in addressing problems, giving the impression that the policy is only thought out and made when problems arise in society.